Evaluation of late‐onset Alzheimer's disease risk variants in mouse models. (December 2021) - Sasner, Michael; Oblak, Adrian L; Garceau, Dylan; Kotredes, Kevin P; Soni, Disha; Lin, Peter Bor‐Chian; Preuss, Christoph; Uyar, Asli; Pandey, Ravi S; Carter, Gregory W; Lamb, Bruce T.; Howell, Gareth R; et al.
Abstract: Background: The MODEL‐AD Center was created to develop, characterize, and distribute more precise preclinical models for late‐onset AD by engineering disease‐associated variants into mouse models, and characterizing the phenotypes using clinically relevant assays (Oblak et al, 2020). While rare familial causative mutations have been known for decades, the genetic etiology of the common (>95%) late‐onset AD (LOAD) is still unknown. Numerous AD risk loci and variants have been identified by large‐scale genetic studies, but few have been functionally verified and models to study their mechanism of action are lacking. Method: Criteria to prioritize risk variants include replication in multiple studies, predicted pathogenicity of variant, sequence conservation between human and mouse, and expression in relevant cell types. We have created variants in coding regions in the Abca7, Clasp2, Kif21b, Mthfr, Mtmr4, Picalm, Plcg2, Shc2, Slc6a17, Snx1, Sorl1 and other loci. Knockouts of Abca7, Ceacam1, Il1rap, Meox2, and Plcg2 have been created to model human loss‐of‐function variants. These variants have been engineered into a mouse model that expresses the AD risk variants APOE4 and Trem2*R47H (as well as a humanized Aβ allele in the newer models). Primary screening was completed by transcriptomic analysis using the nanoString Mouse AD Panel at 4 and 12 months (Preuss et al, 2020). Result: Transcriptomic analysis demonstrated that the Abca7*A1527G, Mthfr*C677T, and Plcg2*M28L models exhibited age‐dependent similarities to transcriptomic changes observed in post‐mortem human samples from the AMP‐AD cohort (Wan et al, 2020). These are now being aged for comprehensive phenotyping at 18 and 24 months of age to include biomarker analysis, transcriptomics, proteomics, metabolomics, in vivo neuroimaging of glucose utilization, blood flow, and amyloid deposition, neuropathology and cognitive assays. Additional models will be added as primary screening is completed. Conclusion: We have screened a significant number of novel models of late‐onset AD and prioritized a few of them for more extensive characterization in old age. All models are made available for both academic and for‐profit use from The Jackson Laboratory, and all validation protocols and data will be shared via the AD knowledge portal (https://adknowledgeportal.synapse.org/ ). For more information see www.model‐ad.org.